As cláusulas abusivas e o Código de Defesa do Consumidor: interpretação como limitação do poder econômico - Croce, Bruno Boris Carlos (2010)
The question of the interpretation of contractual clauses of consumption contracts is a problem faced for the applicator of Law. Specifically on the analysis of an abusive contractual clause it is important to the interpreter to appreciate all available the elements, especially the influence of the economic power in consumer issues. Besides the interpreter are not able to ignore the instrumental capacity of the general clause of good-faith, the absence of the analysis by the judge about the influence of the economic power in contracts harms a effective jurisdictional rendering to real case. The limitation by the applicator of Law to the individual questions and not much relevance given to the economic power as relevant force in the contractual drafting cause deficiency on the interpretation and harm an efficient control of the abusive clauses.